DEVELOPMENT AND IMPLEMENTATION OF PRODUCTION TECHNOLOGY OF REINFORCING THERMOMECHANICALLY STRENGTHENED ROD OF PERIODIC SHAPES NO 16-20, RECEIVED BY MULTISTRAND ROLLING WITH LONGITUDINAL SEPARATION OF BREAKDOWN IN CONDITIONS OF MILL 320 RUP «BMZ» - M. A. Murikov; M. I. Titov; A. V. Rusalenko (Литьë и металлургия)
It is shown that developed and implemented technology of production of multistrand rolled reinforcing hardened rod of periodic profiles No 16-20 allows to produce output of high quality at increasing of capacity of mill 320.